Development Strategy for Waai Tree House Tourist Attractions, Central Maluku Regency - Kalay, Agusthinus; Asthenu, Jean Rosalina; Gomies, Stevanus Johan; Titioka, Stenly Ronaldo; Pattipeilohy, Victor Ringhard; Tousalwa, Carla C.; Sutiksno, Dian Utami (Digital Innovation : International Journal of Management, 2026)
The global tourism industry is experiencing significant growth with a contribution of USD 11.1 trillion to the world's GDP by 2024. Maluku Province has extraordinary natural tourism potential, one of which is the Waai Tree House in Central Maluku Regency which offers a glamorous camping (glamping) concept with the natural beauty of the mountains. Despite having natural advantages, this tourist attraction faces problems of damaged access roads, lack of supporting facilities, and not optimal promotional strategies. This research aims to identify strategic factors through SWOT analysis and formulate effective development strategies to increase the competitiveness of Waai Tree House tourism in a sustainable manner. The research method uses a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews with managers and visitors, visual documentation, and literature studies. The data is analyzed using SWOT analysis to identify strengths, weaknesses, opportunities, and threats, then formulated into four development strategies. The results show the main strengths in the form of natural beauty, unique glamping concepts, and personal service, while the critical weaknesses are damaged road infrastructure and limited facilities. Opportunities include digital promotion and collaboration with governments, while threats include limited accessibility and competition for new destinations. The strategy formulation resulted in four approaches: SO (intensive digital promotion), WO (priority infrastructure improvement), ST (service differentiation), and WT (consistent facility updates) strategy. The implementation of the WO strategy is a top priority with a gradual roadmap of 6-24 months. This research contributes to a contextual strategic framework for the development of glamping tourism in the remote archipelago of Eastern Indonesia.